Handbike: Systematic review and prospective study (Research, Society and Development, 2021)
People with motor disabilities present diverse needs that the available products cannot fully addresses. Handbikes are human-powered vehicles that provide mechanical efficiency and can be used as a product for every day. The objective of this study is to understand how the design aspects of these vehicles have been investigated. As a methodology adopted, a systematic literature review was carried out, in order to find relevant scientific articles on the subject, and a prospective study, to verify the prospective scenario. For the selection criteria adopted, 21 scientific studies and 17 patents, none in Brazil, were found on the research platforms. These results demonstrate that there is potential to work with handbikes in the country due to the market gap.